EVALUATION OF THE INHIBITION ACTIVITY OF SOME LOCAL PLANTS EXTRACT TOWARD THE STAPHYLLOCOCCUS AUREUS - Raid M. Sabeh, Raid M. Sabeh; sahar I.H. , sahar I.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study attempted blocking a pure gelatinase generated by S. aureus using local plant inhibitors. One hundred local isolates of S. aureus, identified through biochemical testing, underwent initial as well as  secondary  testing for identifying actively gelatinase-producing S. aureus  isolates. From these isolates, forty-four exhibiting the highest hydrolysis capacity in the first screening (with a Z/G ratio over 10 mm) were chosen for secondary screening. S. aureus R54 demonstrated the highest specific enzyme activity, recorded at 12.3 U/mg protein. Identified through the Vitek test, this isolate exhibited the highest gelatinase activity. Optimal conditions for gelatinase production via submerged fermentation were determined as follows: medium 1 as the most effective production medium, 2% fructose as the best carbon supplier, as well as A mixture containing 2% extracted yeast with 0.5% nitrogen from peptone . The optimum pH as well as  temperatures had been 9 as well as 37°C.  Following 24 hour incubating, this specific activity attained 54.3 U/mg. Gel filtration chromatography using Sephadex G-150 purified enzyme,  resulting in a 1.2-fold enhancement in purity and An enzyme yielding 98.2%. An isolated enzymatic demonstrated its optimum efficiency at 37°C as well as  maintained stable at this temperature.The isolated enzyme had peak activities at pH 9.0  also maintained stable at pH 7.0. The maximum rate of pure enzyme specificity seen with gelatin. Gelatinase was suppressed by local plant extracts, with avocado extract completely inhibiting 100% of gelatinase activity. It also exhibits antibacterial action against S. aureus R54.